QUALITY OF DENTAL HEALTH CARE - Elkin Javier Ruíz De la Ossa, Odontólogo, Álvaro Antonio Sánchez Caraballo (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The quality of care in dental health is a concept inherent to insurance and refersto the capacity of services to improve the health outcomes of individuals and populations. This approach focuses not only on the optimal dental care provided, but also on the patient experience and the effectiveness of treatments. Objective: To analyze the dental care process from the context of quality. Materials and Methods: Integrative documentary review in the databases Scopus, ScienceDirect, ProQuest and Pubmed, using the descriptors “health quality”, “dental care”, “dental health services”, “health care quality”, and Boolean operators AND and OR, the search was limited to publications from the period 2017 to 2024, in English and Spanish with information about the quality of care and its relationship with dental health, were identified A total of 532 records were collected, of which 99 were selected. Conclusions: The quality of dental health care is an essential component to ensure optimized and effective care for people. The continuous implementation of evidence-based strategies, together with a patient-centered approach, are essential to achieve sustainable improvements for countries’ health systems. Hence, the link between health quality and dental care processes.